Investigation of the Properties of Helical Delay Line using Microwave Office 2000 Package - Daskevicius, V.; Skudutis, J. (Elektronika ir Elektrotechnika, 2000)
Possibility to investigate properties of helical delay lines using Microwave Office is shown. Application of the package allows a number of complimentary factors, such as complex form of the conductor, edge effects, losses in a consider conductor and a dielectric. Package enables to calculate directly the frequence characteristic of the module of transfer coefficient and that of the phase of the investigated helical delay line dependence.